Socialist planning - Ellman, Michael (Cambridge : Cambridge University Press, 2014)
Socialist planning played an enormous role in the economic and political history of the twentieth century. Beginning in the USSR it spread round the world. It influenced economic institutions and economic policy in countries as varied as Bulgaria, USA, China, Japan, India, Poland and France. How did it work? What were its weaknesses and strengths? What is its legacy for the twenty-first century? Now in its third edition, this textbook is fully updated to cover the findings of the period since the collapse of the USSR. It provides an overview of socialist planning, explains the underlying theory and its limitations, looks at its implementation in various sectors of the economy, and places developments in their historical context. A new chapter analyses how planning worked in the defence-industrial complex. This book is an ideal text for undergraduate and graduate students taking courses in comparative economic systems and twentieth-century economic history.
Title from publisher's bibliographic system (viewed on 05 Oct 2015).
Keywords: Economic policy; Comparative economics; Marxian economics; Central planning; Communist countries -- Economic policy